Cultural Identity Formations in Arabic Children’s Literature - Yehia, Rafea Saeid (Journal of Humanities & Social Sciences, 2025)
This article explores the intricate relationship between national identity and environmental identity in Arabic children’s literature, particularly in the context of globalization. It employs a qualitative approach, analyzing existing children’s literature and case studies to understand how globalization impacts these identities. The findings indicate that national identity, defined as a sense of belonging to a specific community with its unique history and culture, is increasingly threatened by globalization. This exposure to diverse cultures can erode cultural specificity, leading to diminished social cohesion. Conversely, environmental identity, which reflects individuals’ connections to their natural surroundings and awareness of environmental issues, is gaining prominence. This identity fosters values of sustainability and collective responsibility for natural resource protection. The article concludes that conflicts between national and environmental identities emerge as societies grapple with preserving cultural characteristics while addressing environmental challenges. The interplay of these identities is particularly significant in Arabic children’s literature, where cultural narratives shape children’s self-awareness and orientation. Arabic children’s literature serves as a critical medium, reflecting the cultural values and traditions of Arab society and contributing to a rich and diverse cultural identity. By embodying children’s daily experiences and cultural interactions, this literature plays a vital role in fostering national pride and environmental consciousness among young readers.